Peranan TPQ Nurul Hidayah Dalam Menanamkan Disiplin Keagamaan Pada Anak di Desa Kebutuh Duwur - Budianti, Septilia Ika; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to determine the role of TPQ Nurul Hidayah in instilling religious discipline in children in Kebutuh Duwur Village, Pagedongan District, Banjarnegara Regency. This research is qualitative research with a research design in the form of descriptive research. The data collection techniques used were interviews, observation and documentation. The data analysis techniques used are data triangulation, data reduction, and drawing conclusions. The results of the research show that the role of the Al-Qur'an Education Park (TPO) Nurul Hidayah Kutasari Kebutuh Duwur Banjarnegara Regency in forming children's discipline in Kebutuh Duwur Village shows that there are supporting factors: (1) when the Ustadz/Ustadzah provides a good role model/uswatun khasanah , (2) there is an attitude of appreciation and support from the community, government, community leaders and neighbors, (3) the facilities and infrastructure are supportive and (4) there is good cooperation and communication between the guardians of the santri, (6) the assistance of the guardians of the santri runs smoothly and well. Syahriah activities, (6) many outstanding students become community role models. Meanwhile, the inhibiting factors are: (1) when the Ustadz/Ustadzah does not provide a good role model, (2) in terms of human resources (HR), namely from students who need special attention and the length of time they need to understand a lesson (3) the condition of students who recite the Koran is still difficult to manage (4) there is no common reading between students and their parents at home, (5) there are still parents who prioritize school lessons rather than reciting the Koran, (6) there is a lack of study space